Experimental research of properties substitute mineral powder made from the sediment sludge complex treatment facilities - Krupko, V.; Kovalchuk, V.; Ostryanskiy, N. (Energy and Automation, 2015)
The properties of experimental substitute mineral powder (which is a part in the production of asphalt mixtures and organic-mineral mixture) manufactured using heat treatment sludge from the activated sludge treatment facilities m. Chernihiv.